Micro-regions of the Lepenski Vir culture: Padina in the Upper Gorge and Hajdučka Vodenica in the Lower Gorge of the Danube - Borislav Jovanović (Documenta Praehistorica, 2008)
This paper was compelled into existence when confronting the fact that the most commonly discussed transitional period connecting the Late Mesolithic and the Early Neolithic in the Đerdap or the Iron Gates Gorges (present-day Serbia and Romania) is determined by the often emphasized lack of adequately published evidence, thus leaving this period largely unknown. We examine previous conclusions concerning the Lepenski Vir culture, or at the very least, try to put such discussions back in their archaeological context. We discuss the features that are essential for the organisation of the settlements, stratigraphy, and adaptability of architecture caused by geomorphology and climate, as well as the remarkable loss of settlement space due to different types of erosion.